2011
DOI: 10.3892/ijo.2011.1277
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol, a natural compound, induces apoptosis of SGC-7901 human gastric adenocarcinoma cells via the mitochondrial and PI3K/Akt signaling pathways

Abstract: Abstract. Gastric cancer is the fourth most commonly diagnosed cancer with the second highest mortality rate worldwide. Surgery, chemotherapy and radiation therapy are generally used for the treatment of stomach cancer but only limited clinical response is shown by these therapies and still no effectual therapy for advanced gastric adenocarcinoma patients is available. Therefore, there is a need to identify other therapeutic agents against this life-threatening disease. Plants are considered as one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 57 publications
3
84
0
Order By: Relevance
“…For example, magnolol suppresses proliferation of cultured human colon cancer cells by inhibiting DNA synthesis 21) ; magnolol-induced apoptotic death is mediated by blocking the EGFR-PI3K-Akt pathway and subsequent activation of the Bad-Bax-cytochrome c-caspase pathway in human prostate cancer cells 18) ; magnolol decreases cell number in a cultured human glioblastoma (U373) cancer cell line 20) ; magnolol (100 µM) induces apoptosis in cultured human hepatoma (Hep G2) and colon cancer (COLO 205) cell lines. 26) More recently, magnolol-induced apoptosis in human gastric adenocarcinoma (SGC-7901) cells by mitochondrial and PI3K-Akt signaling pathways, 27) and magnolol has anticarcinogenic effects against UVB-induced skin tumor development in SKH-1 mice and a possible role in apoptosis during skin tumor development has been determined. 28) However, some studies claim that magnolol-induced cell death occurs via autophagy not apoptosis, 29) and that magnolol increases extracellular-signalregulated kinase (ERK) activity and prevent cells from entering apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, magnolol suppresses proliferation of cultured human colon cancer cells by inhibiting DNA synthesis 21) ; magnolol-induced apoptotic death is mediated by blocking the EGFR-PI3K-Akt pathway and subsequent activation of the Bad-Bax-cytochrome c-caspase pathway in human prostate cancer cells 18) ; magnolol decreases cell number in a cultured human glioblastoma (U373) cancer cell line 20) ; magnolol (100 µM) induces apoptosis in cultured human hepatoma (Hep G2) and colon cancer (COLO 205) cell lines. 26) More recently, magnolol-induced apoptosis in human gastric adenocarcinoma (SGC-7901) cells by mitochondrial and PI3K-Akt signaling pathways, 27) and magnolol has anticarcinogenic effects against UVB-induced skin tumor development in SKH-1 mice and a possible role in apoptosis during skin tumor development has been determined. 28) However, some studies claim that magnolol-induced cell death occurs via autophagy not apoptosis, 29) and that magnolol increases extracellular-signalregulated kinase (ERK) activity and prevent cells from entering apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of neoplasms undergo aberrations in the apoptotic machinery which leads to abnormal cells proliferation (Mashima and (Fulda, 2010;Lawen, 2003;Reed, 2002). Accumulated evidences indicated that most of chemotherapeutic agents halt tumor cells proliferation via induction of apoptosis (Rasul et al, 2013;Rasul et al, 2012a;Rasul et al, 2011a;Rasul et al, 2012b;Rasul et al, 2011d;Rasul et al, 2012b). We examined whether dracorhodin perchlorate inhibited cell growth T24 cells through the induction of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…To reveal the mechanism of the apoptotic effect of TBMS1, Western blotting was done for apoptotic related proteins as previously described (Rasul et al, 2012b;Rasul et al, 2012c). Briefly, A375 cells were incubated with 20 and 40 μM of TBMS1 for indicated time.…”
Section: Western Blottingmentioning
confidence: 99%